Faktor Makro Yang Mempengaruhi Tingkat Pengangguran Terbuka Di Provinsi Banten - Khoiriyah, Siti Alfi Nikmatin; Setiawati, Ririt Iriani Sri (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
Although Banten Province has substantial economic potential driven by its large industrial sector, it continues to face a significant unemployment challenge. This study aims to analyze the various factors that influence the unemployment rate within the province. By using a quantitative research approach, the study applies multiple linear regression analysis through SPSS version 26 to examine the relationship variable independent and variable dependent. Findings from the analysis indicate that factors such as the minimum wage, education level, and economic growth play a significant role in shaping the unemployment rate in Banten Province. These insights are essential for formulating effective policies to reduce unemployment and promote sustainable economic development in the region.